1995
DOI: 10.1016/0014-5793(95)01309-1
|View full text |Cite
|
Sign up to set email alerts
|

Close evolutionary relatedness among functionally distantly related members of the (α/β)8‐barrel glycosyl hydrolases suggested by the similarity of their fifth conserved sequence region

Abstract: Key words: s-Amylase; Glycosyl hydrolase; Conserved sequence region; Evolutionary relatedness eral sequence similarities [9,10]. Four of them, those at or around the strands f13, f14, t5 and t7 of the (ct/fl)8-barrel, are well-known as conserved regions important from both functional and evolutionary points of view [6]. Recently, the fifth conserved sequence region has been pointed out in the sequences of s-amylases [11] to be localised outside the catalytic (0~/fl)8-barrel in domain B comprising the very long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…2). A motif search showed a short stretch ( 209 QPDLN) between the S␤3 and N␣3 regions of PalI which is a proposed selection marker of the ␣-amylase family (9). The sequence alignment with the two OGLs showed that PalI also contains a catalytic triad consisting of three carboxylic amino acids and the two histidine residues essential for enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…2). A motif search showed a short stretch ( 209 QPDLN) between the S␤3 and N␣3 regions of PalI which is a proposed selection marker of the ␣-amylase family (9). The sequence alignment with the two OGLs showed that PalI also contains a catalytic triad consisting of three carboxylic amino acids and the two histidine residues essential for enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…A typical -amylase from A. oryzae (Taka-amylase), like most -amylases, possesses Ca 2þ -binding sites. 26,27) On the other hand, several amino acid residues composing the Ca 2þ -binding site were replaced with other amino acids in the primary structure of MalA. Amino acid substitution can probably alter the Ca 2þ -binding property of MalA.…”
Section: Characterization Of Recombinant Malamentioning
confidence: 99%
“…3). Furthermore, the amino acid sequence of the neopullulanase exhibited the ¢fth conserved sequence region (189-MPDLN) described for the sequences of some K-amylases and related enzymes [20] (Fig. 3).…”
Section: Sequence Of Nplamentioning
confidence: 99%